Conversion Therapy for Advanced Pancreatic Cancer: The Case Series and Literature Review - Wang, Mingxing; Xu, Yunyun; Yang, Min; Jiang, Dingyi; Chen, Yunwang; Jiang, Jiahong; Chen, Zheling; Yang, Liu; Huang, Dongsheng (Frontiers in Pharmacology, 2020)
Background: Pancreatic cancer has a high incidence and mortality. Most patients are in an advanced stage at the time of initial diagnosis and cannot be cured by a single surgery. The ASCO clinical practice guideline emphasized the overall management and multidisciplinary comprehensive treatment which put forward the concept of conversion therapy. In this paper, the real-world observation and study were carried out to explore the conversion effect of chemotherapy in patients with advanced pancreatic cancer and their long-term survival. Methods: The subjects of this study are advanced pancreatic cancer patients who visited the oncology department of Zhejiang Provincial People's Hospital from 2015 to 2019. Collected and summarized the cases, and selected 5 representative patients for analysis, all of them received standard treatment (FOLFIRINOX, AS, AG, or GS). The progress, clinical evaluation, adverse reactions, and prognosis of these patients after conversion therapy were analyzed and discussed in conjunction with relevant literature. Results: Five patients with advanced pancreatic cancer received conversion therapy with an average survival time of 29.8 months, two of them received surgical treatment, and postoperative evaluations were pathological complete response (pCR). The tolerance of chemotherapy was good in five patients, and no serious adverse reactions of grade 3 or 4 occurred. Conclusion: Conversion therapy for patients with advanced pancreatic cancer strives for surgical opportunities of radical resection, prolongs survival and improves quality of life.